Quantifying potassium requirement and removal across crop species - Carciochi, Walter D.; Dobermann, Achim; Cafaro La Menza, Nicolas; Brouder, Sylvie M.; Donough, Christopher R.; Heuschele, Deborah Jo; Oberthür, Thomas; Sandaña, Patricio; Shehu, Bello Muhammad; Pereira, Jessica Thainara S. [UNESP]; Soratto, Rogério P. [UNESP]; Volenec, Jeffrey J.; et al. (Elsevier, 2025)
Context: Potassium (K) management is crucial for addressing global yield gaps in agricultural systems. Objectives: To determine K uptake requirements, K internal efficiency (KIE), and K removal for several crops at different yield targets while assessing the factors driving variation. Methods: We compiled a comprehensive database to determine K requirement, KIE, and K removal for various yield potentials. We assessed intra- and inter-species variations in KIE and compared the K-related parameters across 14 crop species. Results: The K uptake requirements increased with crop yield, with an average two-fold smaller K requirement (22 versus 41 kg K) and 4-fold smaller K removal (3.8 versus 15 kg K) per ton of harvested organ in cereals than soybean. Variations in KIE within crops were related to K harvest index (KHI) in maize and wheat and K concentration in harvested product (KCHP) in soybean. Variation in KCHP across species was related to protein and moisture content. The KIE ranked as follows: cassava and sugarcane (87) > cereals, potatoes, and alfalfa (41−58) > banana and oil-rich crops (10–30 kg kg⁻¹ K). Net K removal increased with higher yield, KHI, and crop residue removal. Conclusions: The K uptake requirement increases with yields, while KIE decreases as yields approach potential yield. Variation in KIE among species derives from differences in KCHP and KHI. Thus, effective K management must consider yield levels, crop choice, and residue management. Significance: We provided a foundation for quantifying K requirements and removals across crop species and target yields, offering essential insights for sustainable K management in agroecosystems.
Keywords: harvest index; internal efficiency; nutrient uptake; potassium concentration; yield